Exploring English Learners’ Hobbies in Helping Them Learn English - R. Adelina Fauzie (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Hobbies are considered important to be one of ways to help English Learners learn English independently. Many English learners do not understand yet things they can explore from their hobbies to help them learn English. Through this study the researcher attempts to explore English learners’ activities when they do their hobbies and to find ideas from them about which part of those activities, they think can help them learn English. The findings show that some English learners taken from respondents can share quite well about activities from their hobbies that can help them learn English, but still many English learners from respondents do not really understand about the relationship of their hobbies with the process of learning English. This condition can be caused by some reasons and as Nezif (2015) says, “It is obvious that there are many challenges in implementing independent learning. The challenges are lack of using authentic materials, a teacher centered approach, lack of learning goals, lack of confidence, high dependence on teachers, lack of practice in self-assessment and peer assessment and lack of interest and lack of learning strategies.” The researcher agrees with Nezif that the challenges are real and by having this study, the researcher tries to figure out what can be planned better for the future to help English learners learn English through their hobbies.